Catalytic ketonization of palmitic acid over a series of transition metal oxides supported on zirconia-based catalysts - Abdul Aleem, Shamina (2022)
Development of sustainable routes to produce bio-based compounds from renewable feedstock is the most relevant strategy to counterbalance the inevitable depletion of fossil resources in the near future. Therefore, the potential of upgrading of bio-based feedstock to produce value added chemicals are highly sought after where ketonization is one of the reactions to convert fatty acids into value added alkanones, ready for subsequent process to yield lubricants, waxes, and specialty chemicals. Current development in ketonization relies heavily on using diluted short chained carboxylic acid as feedstock and very few literatures with fatty acids are found, furthermore current ketonization with fatty acids results in low to moderate yields of ketone with single metal oxides. This study aims to develop ZrO2 based catalysts for the ketonization of palmitic acid to produce elongated ketones as the intermediate in producing high performing bio lubricants. In this work, modification of ZrO2 based catalyst with selected transition metals dopants have shown promising improvement in catalytic activity of palmitic acid ketonization reaction. Small amounts of metal oxide deposition on the surface of ZrO2 catalyst enhances the yield of palmitone (16-hentriacontanone) as the major product with pentadecane as the largest side product. This investigation explores the effects of carefully chosen metal oxides (Fe2O3, NiO, MnO2, CeO2, CuO, CoO, Cr2O3, La2O3 and ZnO) addition as a dopant on bulk ZrO2. The catalysts are prepared via depositionprecipitation method followed by calcination at 550°C and characterized by XRD, BETsurface area, TPD-CO2, TPD-NH3, FESEM, TEM and XPS. The screening of synthesized catalysts was carried out with 5% catalyst loading onto 15g of pristine palmitic acid and the reaction carried out at 340°C for 3h. Screening studies show catalytic activity improvement with addition of dopants in the order of La2O3/ZrO2 < CoO/ZrO2 < MnO2/ZrO2 with the highest palmitone yield achieved using MnO2/ZrO2 catalyst. This is attributed to the existence of intermediate acid and basic sites on the catalyst surface that facilitates the activity of ketonization of palmitic acid. Besides, NiO/ZrO2 exhibits high selectivity exclusively for pentadecane compared to other catalysts with maximum yield of 24.9% and conversion of 64.9% is observed. Optimisation of ketonization shows that reaction temperature and time significantly influence the overall catalytic activity. In conclusion, under the optimized reaction condition of 3h, 340oC and 5% of catalyst loading, highest conversion of 92.3% is achieve with obtained palmitone and pentadecane yield of 27.7% and 10.8% respectively.